Studying Thermal Cracking Behavior of Vacuum Residue - Alrubaye, Saleem Mohammad; Hameed, Mohammed Saadi; Affat, Abdulkareem Dahash (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In the oil industry, the processing of vacuum residue has an important economic and environmental benefit. This work aims to produce industrial petroleum coke with light fuel fractions (gasoline, kerosene , gas oil) as the main product and de asphalted oil (DAO) as a side production from treatment secondary product matter of vacuum residue. Vacuum residue was produced from the bottom of vacuum distillation unit of the crude oil. Experimentally, the study investigated the effect of the thermal conversion process on (vacuum residue) as a raw material at temperature reaches to 500 °C, pressure 20 atm. and residence time for about 3 hours. The first step of this treatment is constructing a carbon steel batch reactor its volume about 700 ml, occupied with auxiliary control devices, joined together with an atmospheric distillation unit. The amounts of light fuel fraction products are 2 vol. % for light gasoline, 4 vol. % for heavy gasoline 17 vol. % for kerosene and 24 vol. % for diesel oil. The second step was the treatment the residue matter from first step, in order to separate the petroleum coke matter from asphaltene matter by solvent deasphalting matter (propane) to prepare de asphalted oil (DAO). The amount of de asphalted oil is about 15 vol. %, leaving asphaltene with impurities to precipitate at the bottom of the reactor and these materials consist of the petroleum coke structure. The petroleum coke separate and calcined at approximately (1000 - 1100) °C, to eliminate the reminder of volatile matter from the industrial coke and reach to commercial property.